2016
DOI: 10.18632/oncotarget.8808
|View full text |Cite
|
Sign up to set email alerts
|

SH003 represses tumor angiogenesis by blocking VEGF binding to VEGFR2

Abstract: Tumor angiogenesis is a key feature of cancer progression, because a tumor requires abundant oxygen and nutrition to grow. Here, we demonstrate that SH003, a mixed herbal extract containing Astragalus membranaceus (Am), Angelica gigas (Ag) and Trichosanthes Kirilowii Maximowicz (Tk), represses VEGF-induced tumor angiogenesis both in vitro and in vivo. SH003 inhibited VEGF-induced migration, invasion and tube formation in human umbilical vein endothelial cells (HUVEC) with no effect on the proliferation. SH003 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…SH003 is a modified traditional herbal medicine that we have recently developed and used to inhibit breast cancer growth and metastasis [24, 30–32]. Our present findings demonstrate that SH003 can also cause the apoptotic cell death of prostate cancer cells.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…SH003 is a modified traditional herbal medicine that we have recently developed and used to inhibit breast cancer growth and metastasis [24, 30–32]. Our present findings demonstrate that SH003 can also cause the apoptotic cell death of prostate cancer cells.…”
Section: Discussionsupporting
confidence: 60%
“…We have also recently shown that SH003 inhibits VEGFR phosphorylation in VEGF-stimulated endothelial cells [32]. Moreover, SH003 also reduces EGFR phosphorylation in MDA-MB-231 breast cancer cells.…”
Section: Discussionmentioning
confidence: 91%
“…Whether the activation of p62 disrupts the Nrf1/Keap1-mediated antioxidant mechanism remains to be investigated. Additionally, previous studies indicated that the silencing of p62 suppressed ROS generation, suggesting that p62 accumulation is related to ROS generation [64][65][66][67]. The current study showed that IAp induced T-47D cell apoptosis and autophagy via cellular Nrf1/Keap1 antioxidant depletion and ROS accumulation ( Figures 6B and 8D,E).…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies have reported on the use of traditional herbal medicines as alternative cancer therapies (6)(7)(8), including a number of studies on HeLa cervical cancer cells that used herbal medicines as therapeutic agents and compounds for potentially treating cervical cancer (9)(10)(11). Our previous study developed a new herbal medicine, called SH003, which is composed of Astragalus membranaceus (Am), Angelica gigas (Ag) and Trichosanthes kirilowii Maximowicz (Tk), based on the principles of traditional Chinese medicine (12,13). Am and Ag have been reported to be effective treatments for a number of diseases, including hematologic diseases, endocrine disorders and cancers (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%